Migrant's remittance and investment financing nexus in Africa: Does investment climate matter? - Chinenye Ifeoma Nwokolo; Matthew Ikechukwu Ogbuagu; Wakeel Atanda Isola (Future Business Journal, 2021)
Development economists have enjoined Africans to leverage on remittance as their main source of investment financing due to its constant and undisrupted inflows despite structural distortions and economic weaknesses compared to other sources of financial flows in recent time. This ignited the motivation for this study, to unveil the nexus between migrant's remittance and investment financing and the modulating effect of the investment climate in this relation on a panel of 28 sub-Saharan African countries over the period 1995 to 2017. Using the panel autoregression distributive lagged estimation technique, the following empirical findings were established. First, the theoretical supposition underpinning the assumption in investment climate as a factor that motivates migrant's remittance inflow to be channelled to investment received a clear empirical support. Second, it was established that the interaction between remittance and components of investment climate (government size and open market) enhanced the growth of private investment. Last, remittance is found to exert a positive effect on private investment in as much as the former does not exceed the threshold of 78%, above which private investment would decline off the quadratic curve. The study suggests the policy-makers channel deliberate efforts at improving not only the efficiency of the market, but government participation especially in the area of tax policy and fiscal financing.
Keywords: E02; E22; F24; O55; P26; 650; Investment climate; Investment financing; Panel data analysis; Remittance; Sub-Saharan region